2015
DOI: 10.3808/jei.201500308
|View full text |Cite
|
Sign up to set email alerts
|

Lab-Scale Experiment and Model Study on Enhanced Digestion of Wastewater Sludge using Bioelectrochemical Systems

Abstract: ABSTRACT. Anaerobic digestion is the slowest process in municipal wastewater treatment, requiring at least 15 days of SRT (solids retention time). Here, we implemented microbial electrolysis cells (MECs) in anaerobic digesters to shorten the long SRT requirement. The MEC bioanode oxidizes acetic acid while the cathode produces H2 gas. The electrode reactions can expedite acetic acid decomposition and thus enhance the rate of biosolids destruction because acetoclastic methanogenesis is known to be the rate-limi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…The vials were sealed with Teflon-lined screw caps and were vortexed for 20 s, and then were placed in a reciprocal shaker at 200 rpm for 24 h to reach the sorption equilibrium. Preliminary experiments showed that 24 h were sufficient for the sorption process to reach equilibrium and the experimental loss of phenanthrene was negligible [28][29][30]. Before testing, the samples were placed for 10 min to separate the soil from the solution.…”
Section: Sorption Studiesmentioning
confidence: 99%
“…The vials were sealed with Teflon-lined screw caps and were vortexed for 20 s, and then were placed in a reciprocal shaker at 200 rpm for 24 h to reach the sorption equilibrium. Preliminary experiments showed that 24 h were sufficient for the sorption process to reach equilibrium and the experimental loss of phenanthrene was negligible [28][29][30]. Before testing, the samples were placed for 10 min to separate the soil from the solution.…”
Section: Sorption Studiesmentioning
confidence: 99%
“…In real-world water-resources planning problems, uncertainties often exist in both parameters and system components (Fan et al, 2015). Some future changes may impact the optimization processes, which need to be taken into account (Asztalos and Kim, 2017;Kong et al, 2017).…”
Section: Two-stage Joint-probabilistic Chance-constrained Programmingmentioning
confidence: 99%
“…The RMSE value for joint distribution can also be determined using Equation (17). The best fitted copula function is the one that has the minimum values of AIC and RMSE.…”
Section: Goodness-of-fit (Gof)mentioning
confidence: 99%
“…In order to identify and analyze uncertainties in hydrological processes, a large number of methods have been proposed in recent decades [12][13][14][15][16][17][18][19][20]. For example, a regional frequency analysis of annual maximum streamflow for Gipuzkoa was developed by Erro and López [21]; the results showed that Gipuzkoa could be characterized by generalized logistic distribution.…”
Section: Introductionmentioning
confidence: 99%